Color Stability of Phycoerythrin Crude Extract (PECE) from Rhodomonas Salina Toward Physicochemical Factors - Endar Marraskuranto; Tri Joko Raharjo; Rina Sri Kasiamdari; Tri Rini Nuringtyas (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
Rhodomonas salina produces Cr-phycoerythrin545 as its designated phycoerythrin (PE) with an absorption maximum at 545 nm and a shoulder 564 nm. PE has potential to be applied as colorants, pharmaceutical agents, and fluorescent dye tags. The stability of the PE color is influenced by the physicochemical factors of the solution. This study aimed to analyze the color stability of PECE against chemical (ethanol and pH) and physical (light and temperature) factors. PECE was prepared from freeze-dried biomass of R. salina and was extracted in phosphate buffer solution (pH = 6.0) using a freeze-thaw method in -25 oC (2 hours) and 4 oC (24 hours). The resulting extract was concentrated and dried in a freeze-dryer. Analyses were conducted using UV-visible and fluorescence spectrophotometer. PECE showed color stability against light of white fluorescent lamp exposure up to 8 hours, temperature exposure up to 40 oC, ethanol solution up to concentration of 20 % (v/v), and pH range 3.9-8.42. Results from this study can be useful for extraction, purification, and future application of Cr-PE545.